Enhanced platelet aggregation and activation under conditions of hypothermia - Xavier, Ruben G; White, Ann E; Fox, Susan C; Wilcox, Robert G; Heptinstall, Stan (Thrombosis and haemostasis, 2007)
The effects on platelet function of temperatures attained during hypothermia used in cardiac surgery are controversial. Here we have performed studies on platelet aggregation in whole blood and platelet-rich plasma after stimulation with a range of concentrations of ADP, TRAP, U46619 and PAF at both 28 degrees C and 37 degrees C. Spontaneous aggregation was also measured after addition of saline alone. In citrated blood, spontaneous aggregation was markedly enhanced at 28 degrees C compared with 37 degrees C. Aggregation induced by ADP was also enhanced. Similar results were obtained in hirudinised blood. There was no spontaneous aggregation in PRP but ADP-induced aggregation was enhanced at 28 degrees C. The P2Y12 antagonist AR-C69931 inhibited all spontaneous aggregation at 28 degrees C and reduced all ADP-induced aggregation responses to small, reversible responses. Aspirin had no effect. Aggregation was also enhanced at 28 degrees C compared with 37 degrees C with low but not high concentrations of TRAP and U46619. PAF-induced aggregation was maximal at all concentrations when measured at 28 degrees C, but reversal of aggregation was seen at 37 degrees C. Baseline levels of platelet CD62P and CD63 were significantly enhanced at 28 degrees C compared with 37 degrees C. Expression was significantly increased at 28 degrees C after stimulation with ADP, PAF and TRAP but not after stimulation with U46619. Overall, our results demonstrate an enhancement of platelet function at 28 degrees C compared with 37 degrees C, particularly in the presence of ADP.